Investigating the Effect of Greenwashing on Green Trust and Green Purchase Intention with the Mediation of Green Confusion and Perceived Risk - Mariam Mola Ghalghachi; Ramin Bashir Khodaparasti (تحقیقات بازار یابی نوین, 2023)
AbstractThe present study examines the effect of greenwashing on green trust and green purchase intention with the mediation of green confusion and perceived green risk. This research is applied in terms of its purpose, it is descriptive-survey in terms of collecting information and it is included in the category of correlational research. The statistical population of the study consists of all consumers of green products in the city of Urmia. Since the statistical population is unlimited, the sample size was selected according to Cochran's formula of 400 consumers by the simple random sampling method. The data collection tool is a standard questionnaire based on a 5-point Likert scale. Data analysis was done with the help of SmartPLS and SPSS software. The results of the analysis of the first and second hypotheses showed that greenwashing has a positive and significant effect on green confusion and green perceived risk. Analysis of the third and fourth hypotheses showed that greenwashing has a negative and significant effect on green trust and green purchase intention. Also, the analysis of the fifth and sixth hypotheses showed that green confusion and perceived green risk have a negative and significant effect on green trust. The analysis of the seventh, eighth, and ninth hypotheses showed that green confusion, green trust, and perceived green risk have a negative and significant effect on green purchase intention. The analysis of mediation hypotheses also showed that all hypotheses have a positive mediation role. IntroductionCompanies engaged in sustainable development usually use green marketing strategies. In fact, green marketing is an essential way to respond to customers who care about environmental concerns, increase green brand image and differentiate their green products. Therefore, green consumers are concerned about environmental issues and make decisions focusing on green attention. Now many partners run a green marketing campaign to beat the competition. In fact, greenwashing refers to the dishonest and misleading claims of the environmental seller. When sellers hide the facts and promote only the positive aspects of their environmental performance, consumers suspect their actions as greenwashing. Therefore, greenwashing is described as the act of misleading consumers about the environmental actions of a company or the ecological benefits of a product or service. Consumers usually base their decisions on advertisements and corporate messages, and on the other hand, greenwashing destroy consumer confidence in green advertisements. Therefore, companies should reduce their greenwashing activities to increase brand image, satisfaction and trust, and should also allow consumers to obtain sufficient and reliable information to enable them to choose products or brands from other companies and check them according to their environmental conditions. Therefore, if green marketers do not provide reliable information to their customers, it will be difficult to convince their customers of the superiority of their products. Customers whose attitude towards green development is high will be able to purchase more green products. In this sense, green purchase intention helps organizations to create a positive brand image, goodwill, and good public image. Based on this, the current research aims to make the consumers of these products gradually change their buying behavior and rethink the products they buy to bring them satisfaction and also be loyal to the purchase of some such products. The present study investigates the effect of greenwashing on green trust and green purchase intention with the mediation of green confusion and perceived green risk. MethodologyThis correlational research is applied in terms of its purpose, descriptive-survey in terms of collecting information. It should be noted that this research was carried out in the field. The statistical population of the research consists of all consumers of green products in the city of Urmia. Since the statistical population is unlimited, the sample size was selected according to the Cochran formula of 400 consumers by the simple random sampling method. The data collection tool is a standard questionnaire based on a 5-point Likert scale. Cronbach's alpha coefficient was used to ensure the reliability of the research variables. All the coefficients obtained for the variables are greater than 0.7, so the reliability of the questionnaire is adequate. Also, to check the face validity, 5 experts (professors from the business management department of Urmia University) were called upon. Data analysis was performed using SmartPLS and SPSS software. Cronbach's alpha coefficient, composite reliability criterion (CR), and average variance extracted (AVE) were used to check the reliability of the external model. The value of composite reliability is greater than 0.7, and the average variance extracted is greater than 0.5, indicating adequate reliability of the model. In addition, the value of the correlation between the indicators and their related structures is higher than the correlation between them and other structures, which is proof of the validity of the corresponding variation in this model. The fit of the structural model of this study was evaluated by fit indexes like the coefficient of determination (R2), the value of predictive validity (Q2), and the goodness-of-fit (GOF) test. According to the analysis results, it can be said that all R2 values are at the average level for the fit of the structural part of the model. The standard value of GOF was calculated as 0.440, which shows the strong fit of the overall research model. FindingsThe findings of the analysis of the first and second hypotheses showed that greenwashing has a positive and significant effect on green confusion and green perceived risk. The analysis of the third and fourth hypotheses showed that greenwashing has a negative and significant effect on green trust and green purchase intention. Also, the analysis of the fifth and sixth hypotheses showed that environmental confusion and perceived green risk have a negative and significant effect on environmental trust. The analysis of the 7th, 8th, and 9th hypotheses showed that green confusion, green trust, and perceived green risk have a negative and significant effect on green purchase intention. The analysis of the mediation hypotheses also showed that all the hypotheses have a positive mediation role. Conclusion Greenwashing is used to show a positive image of a business and to tell the general public that they are not selling questionable goods, thereby avoiding negative feedback. Therefore, customers increasingly distrusted companies' green products. Greenwashing hinders green branding because environmental arguments increase mistrust. Because greenwashing is an obstacle to green marketing, it is difficult for consumers to recognize the effectiveness of green initiatives. In addition, using the incorrect display of the green image leads to an increase in lies and a decrease in customer trust. As a result, customer interest decreases.First, companies must be very strict about their quality standards throughout the production department, which ultimately leads to continuous improvement in product performance. Second, companies should pay more attention to the growing reliance on social media to gain more green trust. Third, companies should reduce corporate greening activities that negatively affect their trusting relationships with consumers. Fourth, companies should ensure the validity of their customers' claims through effective marketing. Manufacturers should educate their consumers and increase their ability to recognize ecological claims. By reducing greenwashing activities related to consumers' quality, functional value, and epistemic value, companies can build strong green trust, which helps them increase green purchase intention and profit sales. Also, if consumers feel conflicted, they can even delay purchasing decisions and can't really trust the business. They postpone their purchases or give up because they are less able to make the right purchase decision. Also, consumer confusion can have a negative impact, one of which is reported distrust. A customer's choice to trust or not trust is influenced by the level of perceived risk. If customers feel a high risk toward a product or brand, the product or brand will not be trusted. In other words, the more risks consumers assess, the less trust they have in products or brands with green claims.